Coupling between the photo-excited cyclic π system and the 4f electronic system in a lanthanide single molecule magnet. Issue 45 (23rd May 2017) - Kizaki, K.; Ozawa, H.; Kobayashi, T.; Matsuoka, R.; Sakaguchi, Y.; Fuyuhiro, A.; Fukuda, T.; Ishikawa, N.
Abstract : Does the angular momentum of the 4f system couple with a photo-induced orbital angular momentum L in the cyclic π system in a lanthanide SMM? Abstract : A new type of electronic interaction which couples two angular momenta, i.e. the angular momentum of a localized 4f system (J ) and an orbital angular momentum generated in a cyclic π conjugated system by irradiation with a circularly-polarized light, has been identified in a lanthanide single molecule magnet.